The Image of Celestina Illustrations, Paintings, and Advertisements - Fernández, Enrique (Toronto Iberic, 2024)
La Celestina, a Spanish literary masterpiece second only in importance to Don Quixote in Spanish literature, has been shaped by the inclusion of images from its very first edition in 1499. The subsequent five centuries were punctuated by many illustrated editions; imaginary portraits of the eponymous procuress Celestina by painters such as Murillo, Goya, and Picasso; and, more recently, screen and stage adaptations. The eponymous character, Celestina, became the prototype from which later representations of procuresses and bawds derived. The Image of Celestina sheds light on the visual culture that developed around La Celestina, including paintings, illustrations, and advertisements. Enrique Fernández examines La Celestina as a mixed-media text, incorporating methods from disciplines such as art history and women's and cinema studies and considers a variety of images including promotional posters, lobby pictures, and playbills of theatrical and cinematic adaptations of the book. Using a visual studies approach, The Image of Celestina ultimately illuminates the culture of Celestina, a mythical figure, who surpasses the literary text in which she originated